Properties of Tin Monosulphide Films Grown by Chemical Bath Deposition. (26th May 2013) - Sreedevi, Gedi; Tulasi Ramakrishna Reddy, Kotte
Abstract : Tin monosulphide (SnS) films have been successfully grown by a simple and low-cost wet chemical process, chemical bath deposition (CBD), using tin chloride and thioacetamide as precursors and tartaric acid as complexing agent. The layers were grown on glass substrate at different bath temperatures (T b ) that varied in the range 50–70°C. The energy dispersive X-ray analysis (EDAX) studies showed that all the grown films were nearly stoichiometric. The X-ray diffraction analysis indicated that the films had an intense peak at 31.6° that corresponds to the (111) plane of SnS and exhibited orthorhombic crystal structure. The intensity of (111) plane increases with the increase in bath temperature and became sharp atT b = 70 °C, where the other crystal planes got suppressed, this indicates better crystallinity of the layers grown at this temperature. No other secondary phases of tin sulphide were observed. The structural parameters such as lattice constants and crystallite size were also calculated. The optical studies revealed that the layers had high optical absorption coefficient (>10 4  cm −1 ). The energy band gap was found to be allowed and direct and varied between 1.30 eV and 1.35 eV. The band gap decreased with the rise in bath temperature. The refractive index and the extinction coefficient were also evaluated. The details of these results will be presented and discussed.